ASME 2012 Internal Combustion Engine Division Spring Technical Conference 2012
DOI: 10.1115/ices2012-81211
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy Logic Control of Diesel Combustion Phasing Using Ion Current Signal

Abstract: Diesel engines have to meet stringent emissions standards without penalties in performance and fuel economy. This necessitated the use of elaborate after treatment devices to reduce the tail pipe emissions. In order to decrease the demand on the after treatment devices, there is a need to reduce the emissions in the formation stage during combustion. This requires a precise control of the phasing of the combustion process. Currently, diesel engines are controlled by pre-set open loop schedules that require ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…In addition to modeling diesel engine combustion phasing, there are also many studies that focus on the control of combustion phasing for diesel engines. 17,2428 Model-based control of combustion phasing was studied in Hillion et al; 17 however, the CA50 reached steady state after more than 20 cycles when the operation condition changed in this study. Willems et al 24 and Yu et al 25 employed proportional–integral (PI) and proportional–integral–derivative (PID) feedback controllers to control the CA50 and indicated mean effective pressure (IMEP) with in-cylinder pressure sensors.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…In addition to modeling diesel engine combustion phasing, there are also many studies that focus on the control of combustion phasing for diesel engines. 17,2428 Model-based control of combustion phasing was studied in Hillion et al; 17 however, the CA50 reached steady state after more than 20 cycles when the operation condition changed in this study. Willems et al 24 and Yu et al 25 employed proportional–integral (PI) and proportional–integral–derivative (PID) feedback controllers to control the CA50 and indicated mean effective pressure (IMEP) with in-cylinder pressure sensors.…”
Section: Introductionmentioning
confidence: 67%
“…Willems et al 24 and Yu et al 25 employed proportional–integral (PI) and proportional–integral–derivative (PID) feedback controllers to control the CA50 and indicated mean effective pressure (IMEP) with in-cylinder pressure sensors. Meanwhile, PI feedback control based on the CA50 estimated by crankshaft torque measurements was used in Thor et al 26 and a fuzzy logic controller was used with an ion current signal to control the location of peak premixed combustion (LPPC), which was studied in Badawy et al 27 While these control approaches worked well, most commercial diesel engines do not have the in-cylinder pressure sensors, crankshaft torque sensors or ion current sensors required for these feedback control techniques. As such, these feedback strategies are still hard to apply in production engines.…”
Section: Introductionmentioning
confidence: 99%
“…Feedback control of CA50 and indicated mean effective pressure (IMEP) has also been examined in Willems et al 27 and Yu et al, 28 but required in-cylinder pressure sensors. Similarly, control of CA50 using feedback from crankshaft torque measurements 29 and control of the location of peak premixed combustion (LPPC) from an ion current signal 30 have also been shown to perform well. However, such sensors are not standard on production engines so the application of these methods may be limited and feedforward control techniques may be more useful.…”
Section: Introductionmentioning
confidence: 97%
“…biodiesel, hydrotreated vegetable oil, etc., which have significantly distinct physical, and chemical properties). 38,39 All the ion current studies mentioned so far were performed under warmed-up conditions. Only a couple of studies were found on the ion current measured during cold-starting of CI engines.…”
Section: Introductionmentioning
confidence: 99%
“…biodiesel, hydrotreated vegetable oil, etc., which have significantly distinct physical, and chemical properties). 38,39…”
Section: Introductionmentioning
confidence: 99%